Adaptation of the Indonesian version of the online cognition scale to measure problematic internet use - Purwati, Dhia Ulfah; Hanifah, Hanifah (Jurnal Ilmiah Psikologi Terapan, 2024)
The internet can make everyday life more accessible; however, it can also cause problematic behavior. It is essential to prevent the negative impact of problematic internet use on daily activities, whether in educational settings, work, social life, or general functioning. This research aims to adapt the Online Cognition Scale (OCS) to the Indonesian language. The number of samples involved in this research was 195 people between the ages of 18-25 years old. This study tested the psychometric properties through content validity tests and obtained S-CVI/Ave results of 0.92 The CFA model fit test index results are within the acceptable value for all goodness of fit indices, with factor loadings between 0.752 - 0.912 for each dimension and 0.318 - 0.882 for each item. There is one invalid item that is eliminated in the Indonesian version of OCS. The coefficient is 1.057, and the coefficient for the four dimensions ranges from 0.770 to 0.878. The coefficient for the four dimensions also moves from 0.792 to 0.881, and the item-total correlation correction test is within the range of 0.427 - 0.702. This measuring tool is used to get an overview of problematic internet usage behavior in Indonesia.